The Future of Work: How Technology is Reshaping the Workforce - Susri,S., M. Erlin (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research investigates the impact of technology on the workplace, human factors, human-computer interaction, as well as the characteristics of the future workplace, by considering various related theories such as Technology Dependency Theory, Technology Acceptance Theory, Activity-Information-Decision-Support Theory, and Ergonomics Theory Cognitive. The results show that technology, including automation and artificial intelligence, is having a significant impact on the way work is done, although it also raises concerns about job replacement and worker well-being. The importance of integrating human factors in digital workplace design as well as worker adaptation to technological changes were highlighted. The implications of this research highlight the importance of organizations paying attention to the balance between technological efficiency and worker well-being, while considering the involvement of technology in supporting decision making and information flow to effectively adapt to technological change. However, this research has limitations related to its focus on limited literature in leading journals, as well as limitations in the analysis of the literature available to date. For future research, a holistic and interdisciplinary approach is recommended as well as further empirical research to deepen understanding of the dynamics of interaction between humans and technology in the workplace.